The Effectiveness Of Vendor Managed Inventory (Vmi) Towards Improving Supply Chain Management (Scm) - A Contract Manufacturer Perspective - SHAFIE, SAZANI (2004)
This study investigates the extent of VMI that may influence Contract Manufacturer performance, particularly the factors of demand sharing, information and strategic partnership, in Supply Chain management.